Cu-induced enhancement of interfacial bonding for brazed diamond grits with NiCr filler alloys. (August 2022) - Xu, Qi; Zhang, Jian; Mao, Cong; Li, Xin; Guo, Fangyu; Zhang, Mingjun; Peng, Ping
Abstract: Restraining diamond graphitization is still the potential problem for brazed diamond tools with NiCr filler alloys. Herein, we systematically investigate the interfacial bonding and mechanical performance of brazed diamond tools with Cu-doping NiCr filler alloys through multi-scale atomistic simulations and experiments. First-principles calculations show that the Cu-doping not only inhibits the structural damage of diamond, but also enhances the metallurgical bonding between diamond and filler alloys. The tensile simulations of Ni-Cr-Cu/diamond interface further verify the strengthening effects of Cu-doping since these bonds of CC within diamond and Ni-Cr-C at interface can withstand greater tensile strains. Combined with molecular dynamics simulations, Cu-doping effectively weaken the graphitization of diamond, which is confirmed through experimental Raman spectroscopy detection. More importantly, the brazed diamond tools by NiCr filler doped with 40 wt% Cu alloy exhibit excellent mechanical grinding performance. These results shed a new light on improving the mechanical properties of brazed diamond tools. Graphical abstract: Unlabelled Image Highlights: Diamond grits are brazed with Cu-doped NiCr filler alloys. Cu doping reduces structural damage of diamond and promote CrC chemical bonding. Cu doping inhibits diamond graphitization upon high temperature and Ni element. The covalent bond between Cr and C becomes stronger after Cu doping. Cu doping improves processing performance of brazed diamond with NiCr alloy.